The experience of learning in space and time. (1st March 2014) - Antonacopoulou, Elena P.
Abstract : Elena P. Antonacopoulou is Professor of Organizational Behaviour at the University of Liverpool Management School where she leads GNOSIS, a research initiative advancing collaborative research in management and organization studies. Her principal research interests include change, learning and knowledge practices in organizations, and the development of new methodologies for studying social complexity. She has successfully secured government and corporate funding that supported a series of international research projects on organizational learning, social practice and dynamic capabilities.